18F-FDG PET/CT and Bone Scintigraphy Findings in Tietze Syndrome. (November 2018) - Oh, Jeong Hee; Park, Soo Bin; Oh, Hong Chul
Abstract : Abstract: We present an interesting image of a 62-year-old woman revealed with Tietze syndrome by 18 F-FDG PET/CT and bone scintigraphy. She presented with right upper chest wall pain with a hard, palpable mass. However, chest radiograph and CT were unrevealing. On PET/CT, intense FDG uptake was noted at the anterior aspect of the right second costal cartilage with dense calcification, which was the correct symptomatic lesion. Bone scan showed increased radioactive uptake at the FDG uptake lesion, but mild uptake was also seen in the asymptomatic lesion.